Quality of life and its selected determinants among elderly people living in nallur divisional secretariat division - Thanujanan, K.; Kamalarupan, L.; Thabotharan, D.; Coonghe, P.A.D. (University of Jaffna, 2018)
Sri Lanka is a one of the fastest aging country in the world. Quality of life is the most appropriate one to examine, the well-being of elderly people. The aim of this study was to assess the Quality of life and socio demographic and health related determinants among elderly people living in Nallur D.S division. A community based descriptive cross sectional study was conducted among 212 elderly people living in their houses. The sample was selected using stratified random sampling technique and participants were interviewed by using an interviewer administered questionnaire. Quality of life was measured by the modified Older People’s Quality of Life Questionnaire (OPQOL). The determinants of Quality of life among elderly population were assessed using Chi square test. In this study male participants (61.3%) were higher than the female (38.7%) and most of the participants fell under the age group of 70-79 years (45.8%). Majority of the participants were married (65.1%) and 80.7% of participants were living with their spouse and children. Nearly half of the (51%) of participants have studied uptoprimary education and nearly 40% of them indicated that their monthly family income was below 15,000/-. More than half of participants (59.4%) rated their health as positive. The most prevalent chronic medical problems were Cataract (30.7%), Hypertension (30.7%) and Diabetic Mellitus (29.2%).The total Quality of life mean score was 132.8 (SD +/- 12.753) out of 180. Factors such as gender, age, marital status, educational level, employment status, living arrangement, monthly family income, Self-Rated Health and presence of chronic medical problems shows the significant relationship with the Quality of life of the participants. It is concluded that the elderly population living in Nallur D. S. Division experience a Neutral level of Quality of life and plan appropriate interventions to improve Quality of life of the elderly people.
Keywords: Elderly people; Jaffna; Nallur; Quality of life; Self-rated health